Disorders of Thyroid Hormones and Lipids in Patients with Type 2 Diabetes in Baghdad City - Athraa Fouad Kaduim (Pakistan Journal of Medical & Health Sciences, 2022)
The aim of the current study was to evaluate thyroid hormone levels and the lipid profile among patients with type-2 diabetes. Venous blood samples were taken from (75) individuals, (50) patients (20 males and 30 females) and (25) healthy individuals as a control group for comparison of results. Serum thyroid hormones and serum lipid profile were estimated for the study groups. The results revealed that S. triglyceride, S. VLDL, S. LDL, S. cholesterol, fasting blood sugar (FBS) levels were significantly elevated (208,83±26.67) mg/dl, (116,19±23,85) mg/dl, (34,79±6,69) mg/dl, (159,22±32,29) mg/dl and (165±14,98) respectively when compared with their levels in the controls, while there was a decrease in serum high density lipoproteins (HDL) levels among patients with type-2 diabetes compared to the controls. A significant decrease was also shown in thyroid hormone levels (T3 & T4) in sera of patients with type-2 diabetes in comparison with their levels in the controls, whereas significant increase was detected in serum TSH hormone levels among type-2 diabetics in comparison with its level in the healthy control group. The study also revealed that (54%) of diabetic patients were affected by thyroid hormone diseases, while (46%) of them were not affected with thyroid disorders. Out of those (54%) type 2 diabetic patients (36%) were females, while (18%) were males. In conclusion, our study showed that there was an obvious effect of thyroid hormone and lipid profile levels on patients with type 2 diabetes. Keywords: Diabetes mellitus, Triglyceride, Thyroid hormones, High density lipoproteins.